Metabolomic Analysis Uncovers Lipid and Amino Acid Metabolism Disturbance During the Development of Ascites in Alcoholic Liver Disease - Cheng, Cheng; Zhou, Ming-xi; He, Xian; Liu, Yao; Huang, Ying; Niu, Ming; Liu, Yi-xuan; Gao, Yuan; Lu, Ya-wen; Song, Xin-hua; Li, Hui-fang; Xiao, Xiao-he; et al. (Frontiers in Medicine, 2022)
Ascites is one of the most common complications of cirrhosis, and little knowledge on ascites-related pathologic metabolism were known. Here 122 alcoholic liver disease (ALD) patients, including 49 cases without ascites, 18 cases with mild-ascites and 55 cases with large-ascites (1) were established according to the International Ascites Club (2), and untargeted metabolomics coupled with pattern recognition approaches were performed to profile and extract metabolite signatures. A total of 553 metabolites were uniquely discovered in patients with ascites, of which 136 metabolites had been annotated in the human metabolome database. 21 ascites-related fingerprints were further identified through the PCA analysis. Moreover, the eigenmetabolite calculated from the 21 metabolites by reducing the dimensions could identify ALD patients with or without ascites effectively. The eigenmetabolite showed a decreasing trend during ascites production and accumulation and was negatively related to the disease progress. These metabolic fingerprints mainly belong to the metabolites in lipid metabolism and amino acid pathway. The results implies that lipid and amino acid metabolism disturbance might play a critical role in the development of ascites in ALD patients and could be a potent prognosis marker.